The Boma: Roger Thurow on global poverty - Part 1 - Thurow, Roger (International Livestock Research Institute, 2023)
Roger Thurow is a senior fellow for global agriculture and food policy for the Chicago Council on Global Affairs. He writes about many of the same issues that animate the work at the International Livestock Research Institute - nutrition, development, hunger, and aid for subsistence farmers. As a writer, Thurow conveys what the lives of the poor are like in vivid, granular detail. We hear from him about what inspired him to focus on these issues - and how he has seen the lives of smallholder farmers change for the better.